Reticulon 4A/Nogo-A influences the distribution of Kir4.1 but is not essential for potassium conductance in retinal Müller glia. (3rd August 2016) - Joly, Sandrine; Dodd, Dana A.; Grewe, Benjamin F.; Pernet, Vincent
Highlights: The expression of Nogo-A is polarized in the radial Müller glia of the mouse retina. Virus-mediated Nogo-A upregulation enhances Kir4.1 immunoreactivity in Müller glia. Nogo-A and Kir4.1 interact in mouse retinae. Nogo-A gene deletion does not change potassium conductance in dissociated Müller glia. Abstract: In the adult retina, we have previously shown that Nogo-A was highly expressed in Müller glia. However, the role of Nogo-A in the glial cell physiology is not clear. In this study, we investigated the possible influence that Nogo-A may exert on other polarized molecules in Müller cells, in particular inwardly rectifying potassium channel 4.1 (Kir4.1) and aquaporin 4 (AQP4) that respectively control potassium and water exchange in glial cells. Our results showed that adenovirus-mediated Nogo-A overexpression with AdNogo-A increased the immunofluorescent signal of Kir4.1 in rat Müller cell line 1 (rMC-1) cells but did not change its expression level by Western blotting. In vivo, AdNogo-A induced ectopic Kir4.1 immunoreactivity throughout the radial processes of Müller cells compared with AdLacZ control virus. Surprisingly, AdNogo-A did not modify the distribution of Dp71 and AQP4 that are common binding partners for Kir4.1 in the dystrophin-associated protein (DAP) complex anchored at the plasma membrane of Müller glia. Immunoprecipitation experiments revealed molecular interactions between Nogo-A and Kir4.1. In Nogo-A KO mouse retinae, the distribution of Kir4.1 was not different from that observed in Wild-Type (WT) animals. In addition, potassium conductance did not change in freshly dissociated Nogo-A KO Müller glia compared with WT cells. In summary, the increase of Nogo-A expression can selectively influence the distribution of Kir4.1 in glia but is not essential for Kir4.1-mediated potassium conductance at the plasma membrane in physiological conditions. Nogo-A-Kir4.1 interactions may, however, contribute to pathological processes taking place in the retina, for instance, after ischemia.